NESTLING BEHAVIOR and PARENTAL CARE of THE COMMON POTOO (NYCTIBIUS GRISEUS) IN SOUTHEASTERN BRAZIL - Cestari, Cesar [UNESP]; Guaraldo, Andre C. [UNESP]; Gussoni, Carlos O. A. [UNESP] (Wilson Ornithological Soc, 2011)
We recorded and quantified the nocturnal activity and parental care of a brooding Common Potoo (Nyctibius griseus) using an infrared camera in southeastern Brazil. Parents alternated care of the nestling and decreased their presence as the nestling grew. Nestling feeding on passing insects while sitting on the nest, movements on the nest, wing exercising, preening, and defecating were recorded primarily while it was alone. The frequency of begging calls per hour was higher when the nestling was accompanied by one of the parents. Nocturnal recordings of this species on the nest revealed behaviors that were not cited in past studies, including: feedings bouts on passing flies performed by the nestling and adults, nestling defecation, and nestling plumage maintenance. The well-known plus newly quantified behaviors of the Common Potoo reinforce their value to survival during the long nestling period. Received 24 May 2010. Accepted 14 September 2010.